2011
DOI: 10.1603/ec10296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Fertilizers on the Life History of Bemisia tabaci (Hemiptera: Aleyrodidae) Biotype B

Abstract: We tested the effects among a purportedly sustainable water-soluble fertilizer, a conventional water-soluble fertilizer, an alternation of these, a controlled-release fertilizer, and a clear water control on the life-history traits of sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae; =Bemisia argentifolii Bellows & Perring) biotype B reared on poinsettia (Euphorbia pulcherrima Willdenow ex Klotzch). Free amino acids in petioles were measured to estimate plant nutrient assimilation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Biswas et al (2009) observed highest number of B. tabaci, per leaf at a higher dose of nitrogen and found a positive correlation between whitefly abundance level and nitrogen dose. England et al(2011) evaluated the influences of sustainable water-soluble fertilizer, a conventional watersoluble fertilizer, an alternation of these, a controlledrelease fertilizer, and a clear water control on the life-history traits of B. tabaci biotype B reared on poinsettia (Euphorbia pulcherrima). The sustainable fertilizer produced plants with the highest concentration of amino acids.…”
Section: Insect Specific Influences Of Major Plant Nutrientsmentioning
confidence: 99%
“…Biswas et al (2009) observed highest number of B. tabaci, per leaf at a higher dose of nitrogen and found a positive correlation between whitefly abundance level and nitrogen dose. England et al(2011) evaluated the influences of sustainable water-soluble fertilizer, a conventional watersoluble fertilizer, an alternation of these, a controlledrelease fertilizer, and a clear water control on the life-history traits of B. tabaci biotype B reared on poinsettia (Euphorbia pulcherrima). The sustainable fertilizer produced plants with the highest concentration of amino acids.…”
Section: Insect Specific Influences Of Major Plant Nutrientsmentioning
confidence: 99%